A ascensão e queda de uma instituição: a SUDENE no sistema federativo brasileiro - Colombo, Luciléia Aparecida (2012)
The thesis statement main purpose is to map the institutional trajectory of SUDENE, from the time when it was created in 1959 by President Kubitschek, up to its dissolution in 2001 by President Fernando Henrique Cardoso. The theory that supported this study is the Brazilian federalism, asymmetrical, from the standpoint of the economic level of their regions. According to SUDENE`s trajectory, the central hypothesis of the research is that institutional changes processed over time contributed to its disintegration and its subsequent elimination. The secondary objective is to provide an overview of the institutional evolution of Superintendent, highlighting the motivations, strategies and conflicts involved in their changes. As a result, it is possible to emphasize that the changes processed during the military regime in 1964 were decisive for the gradual withdrawal of the institutional power. Moreover, with the democratization of the country, the Constitution of 1988 promoted the recovery of federal entities such as states and municipalities, which started to establish unilateral regional development policies, which did not require the mediation of SUDENE. The increase of the transfers of the federal unities, foreseen in the Letter of 1988, it was also decisive for the changing pattern of intervention performed, in which the Federal Government limited to compliance with these constitutional provisions. Thus, the institution lost space as an arena for the articulation of the Northeast regional interests, it was a decisive factor in their it extinction disappearance.